IMPROVING THE QUALITY OF SOFT SKILLS OF SMKS MUHAMMADIYAH 1 KOTA AGUNG STUDENTS THROUGH PUBLIC SPEAKING TRAINING - Rido, Akhyar; Kuswoyo, Heri; Endang Woro Kasih, E Ngestirosa; Lestiani, Shavina; Amalia Sa’adah, Rizma; Anggara Doby Putra, Edho; Parulian Prantinus Kaban, Sahat (Journal of Community Service (JCOS), 2023)
This article addresses the limited access to language activities and the lack of emphasis on public speaking as a soft skill in vocational high school education. It emphasizes the significance of developing public speaking abilities for vocational students to thrive personally and professionally. The article proposes a social community service program that offers public speaking training for vocational students. The program's effectiveness was evaluated using a descriptive qualitative method and questionnaires. The feedback from students indicates positive outcomes in communication skills, confidence, and overall soft skills development. The article concludes that by addressing the deficiency in language activities and focusing on enhancing soft skills, specifically public speaking, vocational students can better equip themselves for the future and improve their prospects in the real world.